The Effectiveness of Influencer Marketing in Promoting Ecotourism in Uganda. A Case Study of Bwindi Impenetrable National Park - Phillip Rukundo (Uganda Christian University, 2025)
Influencer marketing has increasingly been used to shape travel decisions and promote ecotourism. In Uganda the Uganda tourism board has partnered with both local and international influencers to market Bwindi Impenetrable National Park, yet little evidence exists regarding the effectiveness of these campaigns. This study evaluated the role of influencer marketing in promoting ecotourism at Bwindi, with a focus on campaign strategies, content formats, audience engagement, and community impact. A qualitative cross-sectional design was used supported by descriptive statistics using interviews, focus groups discussions, social media content analysis and document reviews. Results show that local influencers such as Fabiola Anita, engaged domestic audiences while international influencers like Khalid al Almeri helped expand global visibility. Short form videos on tiktok and instagram have gained more engagement than the photos. Stakeholders reported modest increases in the inquiries and visitor arrivals during the campaign periods although weak tracking systems made it difficult to attribution to them to bookings. Communities around Bwindi have benefited from greater visibility and craft sales but expressed concerns about unequal advantages and the risk of over tourism. While influencer marketing effectively raises awareness and engagement it requires stronger tracking mechanisms, fair community involvement to maximize sustainable ecotourism outcomes in Uganda. The study examined the relationship between influencer marketing and tourism promotion in Bwindi impenetrable Forest. The objectives were to examine how influencer marketing is used to promote Bwindi, to examine the relationship between influencer campaigns and tourism, to identify the most effective influencer campaigns. The study used the social influencer and source credibility theories. A qualitative design was used to collect data from 24 tour operators. Findings revealed that influencer marketing is promoted through content on the online pages of the influencers. Influencers marketing improve tourism and short videos and reels are the most effective. Inconclusion influencer marketing improves tourism. It’s recommended that influencers use short videos and reels as they are most effective
Undergraduate Research